Prevention, Detection and Management of Oral Cancer 2019
DOI: 10.5772/intechopen.87091
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Proliferation and Energy Metabolism in Oral Cancer

Abstract: Human oral squamous cell carcinoma (HOSCC) is the most common head and neck malignant neoplasm. Therapy is generally performed in multidisciplinary approach that used chemotherapy, radiotherapy, and surgery against patients with oral cancer; however, we cannot avoid dysfunction due to its side effects or surgical defects, and it significantly impacts the postoperative quality of life, unfortunately. Therefore, a better understanding of the molecular mechanisms driving oral carcinogenesis may lead to new diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…The results were expressed in δ values. For carbon isotopes, we obtained the δ 13 C values by comparing the 13 C/ 12 C ratio in the analysed sample to the isotopic ratio 13 C/ 12 C ratio in the international PDB standard (Pee Dee Bee, Belemnitella Americana). For nitrogen isotopes, we used δ 15 N values related to the 15 N/ 14 N ratio of the standard, which is the atmospheric nitrogen.…”
Section: Irms Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were expressed in δ values. For carbon isotopes, we obtained the δ 13 C values by comparing the 13 C/ 12 C ratio in the analysed sample to the isotopic ratio 13 C/ 12 C ratio in the international PDB standard (Pee Dee Bee, Belemnitella Americana). For nitrogen isotopes, we used δ 15 N values related to the 15 N/ 14 N ratio of the standard, which is the atmospheric nitrogen.…”
Section: Irms Proceduresmentioning
confidence: 99%
“…Studies have also confirmed changes in the metabolism of oral cancer cells, revealing that oncogenic signalling pathways directly promote metabolic reprogramming to increase the biosynthesis of lipids, carbohydrates, proteins, DNA, and RNA, leading to increased tumour growth [ 12 ].…”
Section: Introductionmentioning
confidence: 99%